Normal left atrial strain and strain rate using cardiac magnetic resonance feature tracking in healthy volunteers. (23rd June 2019) - Truong, Vien T; Palmer, Cassady; Wolking, Sarah; Sheets, Brandy; Young, Michael; Ngo, Tam N M; Taylor, Michael; Nagueh, Sherif F; Zareba, Karolina M; Raman, Subha; Mazur, Wojciech
Abstract: Aims: The aim of our study was to establish normal ranges for left atrial (LA) strain and strain rate using cardiac magnetic resonance feature tracking (CMR-FT), LA sphericity index, and to compare LA strain using CMR-FT with 2D-speckle tracking echocardiography (STE) in a healthy population. Methods and results: A total of 112 volunteers (45 male, 67 female) had adequate tracking for analysis on CMR-FT (Circle Cardiovascular Imaging, Calgary, Canada). The median age was 42 years (range 19–79 years, interquartile range 30–53 years). LA reservoir, conduit, booster strain, strain rate using CMR-FT, and sphericity index were evaluated. Of the 112 volunteers, 91 patients had adequate tracking on 2D-STE using three commonly applied zero-baseline time reference methods: R-R gating, P-P gating, and volume gating (defining end-systole at the LA maximum and end-diastole at the LA minimum). The LA strain, strain rate using CMR-FT, and sphericity index were reported and comparable between both genders ( P > 0.05 for all). The LA booster function including strain and strain rate increased significantly with age ( P < 0.001 for all), while the LA conduit function gradually decreased. In comparison with STE, the LA reservoir strain was comparable between CMR and volume-gating methods (38.48 ± 9.31 vs. 36.77 ± 6.46; P = 0.13) but not with R-R and P-P gating methods ( P < 0.001 for all). LA strain, strain rate, and sphericity index using CMR-FT had good intraobserver and interobserver reproducibility. Conclusion: LA strain, strain rate using CMR-FT, and sphericity index can be quickly assessed with good intraobserver and interobserver reproducibility.